SCHOULID : Indonesian journal of school counseling - Ikatan Konselor Indonesia (Ikatan Konselor Indonesia (IKI), 2016)
Research, theory, or program applications pertinent to school counseling and people who have interests in all areas of counseling and school development. The aim of this journal is to give design and support for school counselor efforts to help students focus on academic, career and social/emotional development so they achieve success in school and are prepared to lead fulfilling lives as responsible members of society.
Keywords: Educational counseling : Indonesia : Periodicals; Educational counseling : Periodicals; Student counselors : Periodicals; Educational counseling; Student counselors; Indonesia; Theory & Practice of Education